Sex-differences in the prevalence of Helicobacter pylori infection in pediatric and adult populations: Systematic review and meta-analysis of 244 studies - Abubakar, I (2017)
Background: The main outcome of Helicobacter pylori infection, i.e. gastric cancer, is more frequent in men, but there is no comprehensive synthesis of the evidence on a potential role of sex in the acquisition and/or persistence of infection. Aims: To quantify the association between sex and H. pylori infection in pediatric and adult populations, through systematic review and meta-analysis. Methods: PubMed® was searched, from inception to September 2015, to identify population-based studies reporting the prevalence and/or incidence of H. pylori infection in both sexes. Odds ratios (OR) or data to compute them were extracted; adjusted estimates were preferred, whenever available. The DerSimonian and Laird method was used to compute summary estimates and respective 95% confidence intervals (95%CI), separately for children and adults. Results: Among a total of 244 studies, mostly cross-sectional, male sex was associated with a greater prevalence of H. pylori infection, both in children (102 studies, OR = 1.06, 95%CI: 1.01, 1.12, I2 = 43.7%) and adults (169 studies, OR = 1.12, 95%CI: 1.09, 1.15, I2 = 68.5%). An underrepresentation of studies showing a negative association between male sex and infection was observed (Egger’s test: p = 0.006). Conclusions: Although further research is needed to understand the mechanisms by which sex may influence the acquisition and/or persistence of infection, our results support a small contribution of sex differences in the prevalence of infection to the male predominance of H. pylori-related outcomes, including gastric cancer.